Neck-Sealing in early Islam - Robinson, Chase (Journal of the economic and social history of the Orient, 2005)
Abstract Arabic and Syriac sources for early Islam, especially for seventh- and eighth-century Syria and Iraq, describe the use of neck sealings in the administration of the poll tax, which was levied upon non-Muslims. This article evaluates the relevant literary, historical and material evidence, including some surviving sealings, and proposes that at origin, neck-sealing related to other stigmatizing practices, and was principally symbolic and punitive. Des texts arabes et syriques, particulièrement originaires de la Syrie et de l'Iraq des septième et huitième siècles, décrivent l'usage des sceaux en pendentif pour l'application de la capitation qui était imposée aux non-musulmans. Cet article étudie les sources littéraires, historiques et archéologiques, y compris des sceaux qui nous restent, et suggère que à l'origine, les sceaux étaient liés à d'autres pratiques discriminatives/stigmatisantes, et étaient avant tout symboliques et punitives.